2019
DOI: 10.1016/j.foodres.2018.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Extruded sorghum consumption associated with a caloric restricted diet reduces body fat in overweight men: A randomized controlled trial

Abstract: This study aimed to evaluate the effect of sorghum intake on body composition and metabolic variables in overweight men. In a randomized controlled crossover study, 24 overweight men (25.6 ± 4.6 years) were randomly allocated into one of two treatments: extruded sorghum or extruded wheat. The study consisted of 2 periods of 8 weeks with at least 4 weeks of washout. Anthropometric, clinical and metabolic risk variables were assessed at baseline and at the end of each intervention period. Extruded sorghum consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Interestingly, a sorghum drink containing high levels of proanthocyanidin (condensed tannins) performed better than the two other sorghum drinks that did not contain proanthocyanidins at reducing blood glucose [ 12 ]. Human clinical trials also indicated that consumption of flaked biscuits made from whole grain sorghum led to higher satiety compared to participants receiving the wheat treatment [ 13 ] and consumption of extruded sorghum combined with a calorie-restricted diet significantly promoted weight loss and decreased waist circumference and body fat percentage and performed better than wheat [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a sorghum drink containing high levels of proanthocyanidin (condensed tannins) performed better than the two other sorghum drinks that did not contain proanthocyanidins at reducing blood glucose [ 12 ]. Human clinical trials also indicated that consumption of flaked biscuits made from whole grain sorghum led to higher satiety compared to participants receiving the wheat treatment [ 13 ] and consumption of extruded sorghum combined with a calorie-restricted diet significantly promoted weight loss and decreased waist circumference and body fat percentage and performed better than wheat [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finger millet, foxtail millet, barnyard millet, and/or a mixture of millets (finger millet and little millet) were used in the 19 studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) that were included in one or more outcomes of meta-analysis. It was observed that consumption of milletbased food for a duration varying from 21 days to 4 months had a significant reducing effect on TC, triacylglycerol, VLDL-C, and/or LDL-C levels.…”
Section: Resultsmentioning
confidence: 99%
“…In the catechines class, green tea and coffee were also reported for the significant reduction of body weight and maintenance of the body weight in average condition. Sorghum bicolor L. has been demonstrated to be a worthy substitute to control obesity in weighty men because it reduces body fat fraction and amplifies daily carbohydrate and dietary fiber consumption when compared to wheat consumption [ 169 ]. Nowadays, people are having a great interest in herbal plant compositions or phytochemicals due to safer and efficacious effects, and the clinical studies must not be limited to in vitro or in vivo levels for their development.…”
Section: Clinical Studies: Translational Potential Of Natural Product...mentioning
confidence: 99%